Polythiophene blends and composites as potential energy storage materials - Shindalkar S.S. (Elsevier Ltd, 2024)
Customer growth in the global electronic market is accelerating, particularly for wearable and portable fancy gadgets. This trend has given substantial motivation for the development of more efficient and low-cost energy storage devices such as supercapacitors, sensors, and printed circuit boards. Conducting polymers (CPs) meet all of the above specifications, making them a promising material of study for electronic manufacturers among which polythiophene is one of the most preferred CPs due to its versatility, comparatively better environmental stability, and significant flexibility to change performance as needed. Polythiophene has higher electrical conductivity than other CPs invented to date, such as polypyrrole and polyaniline, with values ranging from 300 to 500 S/cm. Electron conjugation is the primary cause of electrical conduction, and polythiophene provides flexibility in varying this phenomenon simply by attaching different functional groups, which is impossible with other conducting polymers. This review summarizes recent work done in engineering of polythiophene blends and composites and their electrochemical performance followed by respective application. The specific capacitance of virgin PEDOT (poly (3, 4-ethylenedioxythiophene) nanofiber is 20 F/g, which can be increased by nearly 18 folds